1994
DOI: 10.1021/bi00194a016
|View full text |Cite
|
Sign up to set email alerts
|

GDP As a Regulator of Phosphorylation of Elongation Factor 1 by Casein Kinase II

Abstract: Elongation factor 1 (EF-1) consists of four subunits: the alpha subunit catalyzes the GTP-dependent binding of aminoacyl-tRNA to ribosomes while the beta, gamma, and delta subunits catalyze GDP/GTP exchange on EF-1 alpha. Phosphorylation of the beta subunit of EF-1 from rabbit reticulocytes by casein kinase II was stimulated up to 22-fold by polylysine, while basic proteins or polyarginine enhanced phosphorylation to a lesser extent. When physiological components of protein synthesis were examined as potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The lack of an effect by GDP is consistent with the availability of ␤ and ␦ in the reconstituted complex for phosphorylation by CKII as compared with EF-1. In the same study (35), polylysine was shown to stimulate phosphorylation of ␤ in native EF-1 but not ␦. With the recombinant subunits, polylysine stimulated phosphorylation of ␤ but not the ␦ subunit (data not shown), which is consistent with the studies on native EF-1.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The lack of an effect by GDP is consistent with the availability of ␤ and ␦ in the reconstituted complex for phosphorylation by CKII as compared with EF-1. In the same study (35), polylysine was shown to stimulate phosphorylation of ␤ in native EF-1 but not ␦. With the recombinant subunits, polylysine stimulated phosphorylation of ␤ but not the ␦ subunit (data not shown), which is consistent with the studies on native EF-1.…”
Section: Discussionmentioning
confidence: 78%
“…Previously, Palen et al (35) showed that GDP stimulated the phosphorylation of the ␤ and ␦ subunits of native EF-1 by CKII. Such a stimulation was not observed with the recombinant subunits or reconstituted ␤␥␦.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EF-1␦, therefore, plays a key role in protein synthesis by regulating the activity of EF-1␣. EF-1␦ is phosphorylated by several cellular protein kinases, including cdc2, casein kinase II (CKII), protein kinase C, and multipotential S6 kinase (3,29,35,46). Studies on the phosphorylation of EF-1␦ suggest that these modifications of the protein alter translational efficiency (3,26,46,47).…”
mentioning
confidence: 99%
“…The ␤ and ␦ subunits are also phosphorylated by protein kinase CKII (13)(14)(15)(16). GDP has been shown to enhance the phosphorylation of ␤ and ␦ by CKII, while little phosphorylation is observed in the absence of GDP (16).…”
mentioning
confidence: 99%